The Occurrence of Cultivated Plants in the Region of Styria from the Palaeolithic till the Middle Ages - Paušič, Andrej; Šušek, Andrej (Agricultura Scientia, 2021)
The aim of this review study was to analyse large paleo-botanical datasets derived from investigations of 35 archaeological sites and published during a longer time period. The presence of 18 selected crop taxa has been monitored in the region of Styria. Our results indicate that in the Copper Age, the cultivation and usage of proso millet (Panicum miliaceum) and the einkorn wheat (Triticum monococcum) was present. From the Bronze Age period, the most commonly grown taxa are barley (Hordeum vulgare), proso millet, emmer wheat (Triticum dicoccum) and spelt wheat (Triticum spelta). In the Iron Age, some new crops emerged along with the already common foxtail millet (Setaria italica) and common flax (Linum usitatissimum), a species first found in Styria during this exact period. The importance of Roman period for Styria lies in the introduction of new taxa like the Persian walnut (Juglans regia), of which remnants were also found in the studied area. The late Antiquity and Middle Ages are a wide time frame where all important cereal taxa were already known from previous periods and were also grown in the studied area, with the exception of oat (Avena sativa) and durum wheat(Triticum durum), of which remnants were absent from this period.
Keywords: archaeobotany; biogeography; crop domestication; paleobotany; Styria